(untitled) (Journal of Society of Surgeons of Nepal, 2019)
Choledochal cysts are rare congenital anomalies that have a variable presentation with occasional diagnostic and therapeutic dilemmas. Our case is a 14-year female presented with recurrent abdomen pain with confusing diagnostic findings, suggestive of a large choledochal cyst (22x29x17cm) initially managed by percutaneous tube biliary drainage and later underwent excision and HPE revealing non-malignant findings. The choledochal cyst should always be a differential diagnosis for any patient presenting with an abdominal mass and should be managed accordingly.